2009
DOI: 10.3126/jowe.v3i0.2225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Limiting Factors on Phytoplankton and Coliform Population in an Inundated, Isolated Wetland

Abstract: The relationships of phytoplankton with physical (temperature, pH), chemical (dissolved oxygen, phosphate, sulphate and nitrate) and biotic (total and fecal coliforms) parameters were analysed for the year September 2007 to August 2008 in a seasonally inundated, isolated wetland -Malwar which is situated between 22° 36'55.78" N and 72°54'58.01" E; about 7 kilometres from Anand, near KanjariBoriyavi railway station, Central Gujarat, India. Phytoplankton species belonged to Cyanophyceae, Chlorophyceae, Bacillari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…A comparatively high pH exists in Pond 1, which may be associated with the abundance of Bacillariophyceae, in agreement with the finding of Kumar and Oommen () that acidic water does not support Bacillariophyceae abundance. There was an abundance of Bacillariophyceae in Pond 1 associated with nutrients, particularly phosphate, as per the finding of Tavares et al .…”
Section: Resultssupporting
confidence: 88%
“…A comparatively high pH exists in Pond 1, which may be associated with the abundance of Bacillariophyceae, in agreement with the finding of Kumar and Oommen () that acidic water does not support Bacillariophyceae abundance. There was an abundance of Bacillariophyceae in Pond 1 associated with nutrients, particularly phosphate, as per the finding of Tavares et al .…”
Section: Resultssupporting
confidence: 88%
“…Predominance of Bacillariophyceae species throughout the period under analysis has been associated with alkaline water, because acidic waters do not support an abundance of species and show high activity at relatively low temperature (Allen et al, 2005). Kumar and Oommen (2009) reported that acidic waters do not support an abundance of Bacillariophyceae, whereas their density is higher in alkaline waters, with pH above 8.0, and diatom growth is stimulated by nitrate. In this investigation alkaline pH (between 7.2 and 8.8) except at P 3 in October, and high nitrate concentrations, supported a high population of diatoms.…”
Section: Sc F Sc F Sc F Sc F Sc F Sc F Cladoceramentioning
confidence: 99%
“…The plankton community, on which the whole aquatic population depends, is largely affected by an interaction of a number of limiting factors such as low dissolved oxygen, moderate sulphate, nitrate, phosphate and other factors (Kumar and Oommen, 2009). …”
Section: Sc F Sc F Sc F Sc F Sc F Sc F Cladoceramentioning
confidence: 99%
“…(Kumar and Omen, 2009). The nitrogen and phosphorous plays dominant role in controlling the growth and abundance on phytoplankton and freshwater angiosperms.…”
Section: Introductionmentioning
confidence: 99%